Correlated defect nanoregions in a metal-organic framework - Cliffe, M; Wan, W; Zou, X; Chater, P; Kleppe, A; Tucker, M; Wilhelm, H; Funnell, N; Coudert, F-X; Goodwin, A (Springer Nature, 2014)
Throughout much of condensed matter science, correlated disorder is a key to material function. While structural and compositional defects are known to exist within a variety of metal–organic frameworks (MOFs), the prevailing understanding is that these defects are only ever included in a random manner. Here we show—using a combination of diffuse scattering, electron microscopy, anomalous X-ray scattering and pair distribution function measurements—that correlations between defects can in fact be introduced and controlled within a hafnium terephthalate MOF. The nanoscale defect structures that emerge are an analogue of correlated Schottky vacancies in rocksalt-structured transition metal monoxides and have implications for storage, transport, optical and mechanical responses. Our results suggest how the diffraction behaviour of some MOFs might be reinterpreted, and establish a strategy of exploiting correlated nanoscale disorder as a targetable and desirable motif in MOF design.